2018
DOI: 10.1016/j.str.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Recruitment of Ctf18-RFC to the Replisome

Abstract: Ctf18-RFC is an alternative PCNA loader which plays important but poorly understood roles in multiple DNA replication-associated processes. To fulfill its specialist roles, the Ctf18-RFC clamp loader contains a unique module in which the Dcc1-Ctf8 complex is bound to the C terminus of Ctf18 (the Ctf18-1-8 module). Here, we report the structural and functional characterization of the heterotetrameric complex formed between Ctf18-1-8 and a 63 kDa fragment of DNA polymerase ɛ. Our data reveal that Ctf18-1-8 binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 52 publications
1
61
0
Order By: Relevance
“…This showed that Ctf18-1-8 forms a tight complex with Pol2 CAT with a K D of 40 nM (Fig. 1D), over 30-fold stronger than the 1.3 µM K D measured for the truncated Pol2(1-528) construct (Grabarczyk, Silkenat and Kisker, 2018).…”
Section: Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…This showed that Ctf18-1-8 forms a tight complex with Pol2 CAT with a K D of 40 nM (Fig. 1D), over 30-fold stronger than the 1.3 µM K D measured for the truncated Pol2(1-528) construct (Grabarczyk, Silkenat and Kisker, 2018).…”
Section: Resultsmentioning
confidence: 82%
“…Previously, we showed that yeast Ctf18-1-8 forms a relatively transient complex with a truncated construct of the Pol ε catalytic domain, Pol2(1-528) (Fig, 1A), through the WH3 domain of Dcc1 (Dcc1 WH3 ) and exonuclease domain of Pol2 (Pol2 EXO ) (Grabarczyk, Silkenat and Kisker, 2018). Although this minimal complex could be disrupted in vitro by a structure-guided triple mutation, Dcc1 R367A/R376A/R380A (henceforth Dcc1-3A) (Grabarczyk, Silkenat and Kisker, 2018), a new crystal form of this complex revealed that this interface is highly flexible (Figure S1A). We therefore used cryo-EM to solve the structure of Ctf18-1-8 in complex with the complete catalytic domain of Pol2 (residues 1-1192, henceforth Pol2 CAT ) to 4.2 Å resolution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations